Characterization of the substrate and interstitial water of Mata de Limón mangrove, Puntarenas, Costa Rica - Guzmán-Sánchez, Yixlen (2023)
Mangroves are systems that, through land-sea interaction, vary in time and are highly productive. The objective of the study was to describe the granulometry, physicochemical parameters, and nutrients of the Mata de Limón Wetlands. In 2014, six monitoring plots were established to analyze the sediments, nutrients and physicochemical parameters. A greater presence of sand was found, especially thick sand. The pH values were very similar, most of them close to 8, while oxidation-reduction values showed a predominance of reductive processes with a minimum value of -54 and a maximum value of -3 mV. Regarding nutrients, the maximum concentration of ammonium was 29.2 μmol/L, while the minimum was zero. In the case of nitrate, the highest was 30.53 μmol/L and the lowest was 1.01 μmol/L. For both phosphates and silicates, the maximum values were 21.59 and 174.95 μmol/L, and the minimum were 0.71 and 19.66 μmol/L, respectively. The Mata de Limón Wetlands are comprised mainly by sand; the physicochemical parameters are affected by spatiotemporal variations and a high quantity of nutrients. Nevertheless, it is disturbed by anthropogenic pressures, causing instability in the evaluated variables, which increases their complexity; on the contrary, the river system corresponds to a more stable pattern with predictable changes to the interior of the ecosystem.